Fatores associados ao câncer de boca: um estudo de caso-controle em uma população do Nordeste do Brasil - Andrade, Jarielle Oliveira Mascarenhas (2014)
INTRODUCTION: Oral cancer is a public health problem in Brazil and around the world. Its etiology is multifactorial, tobacco and alcohol are the most important risk factors; in addition, solar radiation, HPV, diet and social conditions has been listed as risk factors for the development of this neoplasm. OBJECTIVE: This research aims to know the association between factors such as: age, sex, skin color, occupation, marital status, level of education, place of residence, use of tobacco, alcohol consumption and oral cancer in subjects attended in Reference Center for Oral Lesions, of the Brazil’s Northeast since 2002 to 2012. METHODOLOGY: This study is a case control study. The cases were formed by all population of subjects attended in this Center, with histopatologycal diagnose of oral squamous cell carcinoma, that it corresponds 127 individuals. The control group was consisted of 254 individuals from the same reference center where cases were recruited with other diseases, but without oral cancer or premalignant lesions. It considered two controls for each case. Cases and controls were adjusted by sex and age. After collecting the data it was performed univariate analysis, after the bivariate analysis (Chi Square test of Pearson) to determine the association between the dependent variable (oral cancer) and the independent variables; odds ratios (OR) and confidence interval of 95% were calculated. Finally, in the multivariate analysis was used hierarchical model with logistic regression to evaluate the interrelationships between the independent variables and oral cancer, considering the blocks of distal and proximal variables. RESULTS: The results showed that consuming more than 20 cigarettes per day [OR = 6.64; CI =2.07-21.32], high intake alcohol [OR= 3.25; CI =1.03-10.22] and the synergistic use of tobacco and alcohol [OR = 9.65; CI= 1.57-59.08] are the most important risk factors for oral cancer. CONCLUSION: The associated factors for oral cancer were smoking and drinking. Socio-demographic factors were not associated with oral cancer after adjustment for smoking and alcohol consumption.